Managing multimedia collections and services in IIUM Library: staff enthusiasm positively contributes - Md Amin, Norasiah (Persatuan Pustakawan Malaysia, 2005)
Human heritage is kept in various physical formats. Before the 1980s, librarians handled mainly printed collections and very few non-printed materials such as microform, video and audiocassettes. With the advancement of information technology, especially after the late 1990s, information is now stored in a variety of physical formats, such as, diskettes CD-ROMs and DVDs. Ultimately, librarians must manage this variety of collections and offer related services. Although managing multimedia materials and services poses a great challenge, the author believes that human resources can overcome those challenges through continuous support and motivation from the middle and top managers. This article is written in order to share the author ’s views and experience of managing the multimedia collections and services from 2001 to 2004 at the Main Library of the International Islamic University Malaysia (IIUM).